1985
DOI: 10.1007/bf00414110
|View full text |Cite
|
Sign up to set email alerts
|

Phenylalanine and UVA light for the treatment of vitiligo

Abstract: The administration of phenylalanine (Phe) combined with UVA exposure was found to be effective in vitiligo. Phe is an amino acid which constitutes part of the daily dietary protein, and when orally administered in a dose of 50 mg/kg body weight, it results in an elevated plasma level. Since peak concentrations of Phe in the blood are reached between 30 and 45 min after ingestion, UVA exposure was administered at this time. After 4 months (32 treatments) reasonable repigmentation preferentially occurred in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

1994
1994
2006
2006

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 15 publications
1
20
0
2
Order By: Relevance
“…Normal fasting L-Phe levels were similar to those re ported by Perry et al [15] and to our previous study [7], L-Phe loading resulted in high sustained plasma L-Phe lev els and a slightly elevated tyrosine level as reported earlier by us [7] and by Biella and Haustein [11], The plasma L-Phe level was higher with increased L-Phe doses. Blau et al [ 16] also observed high sustained levels of plasma L-Phe with no rise or a slight rise in plasma tyrosine levels with L-Phe loading.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Normal fasting L-Phe levels were similar to those re ported by Perry et al [15] and to our previous study [7], L-Phe loading resulted in high sustained plasma L-Phe lev els and a slightly elevated tyrosine level as reported earlier by us [7] and by Biella and Haustein [11], The plasma L-Phe level was higher with increased L-Phe doses. Blau et al [ 16] also observed high sustained levels of plasma L-Phe with no rise or a slight rise in plasma tyrosine levels with L-Phe loading.…”
Section: Discussionsupporting
confidence: 73%
“…Time, min The highest peak values 275.7 ± 62.7 pmol/1 with 50 mg/kg [7], 406.5±24.9 pmol/l with 70 mg/kg (n = 12) and 639.7± 29.3 pmol/1 with 100 mg/kg (n = 16) were achieved at 45 min, 1 h and 45 min, respectively. The average tyro sine level kept on increasing slightly as long as 3 h after the ingestion of ¿-Phc and was not proportional to the dose of ¿-Phe ( fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Its plasma level is found to be elevated 30-45 minutes after ingestion at the dosage of 50 mg/kg body weight (89). UVA exposure at that time or exposure to midday sun for 30 minutes may result in reasonable pigmentation after several sittings (90,91).…”
Section: Phenylalanine and Uva (Pauva)mentioning
confidence: 98%